Reconsidering Context in Psychedelic Research: Ritual Emergent Mechanisms and the Unified Field - Lutz, Heather (Journal of Scientific Exploration, 2023)
The outcomes of recent psychedelic research have been attracting more public attention in the media along with more private funding. This research is primarily being conducted in a clinically administered setting while attention to context has largely been ignored. Entheogens have been used by indigenous peoples in ritual settings as far as recorded history can be found. Modern clinical use has only been occurring within the last century. This leaves much to explore in terms of the context in which such a potent treatment has effect. This manuscript conceptualizes entheogenic spiritual rituals as ancient libraries of healing knowledge. It examines the therapeutic use of psychedelics from both the biomedical perspective of the diagnosis and treatment model contrasted with the ritual context. It discusses a number of explicit and implicit ritual attributes that may play a role in the healing process. Additionally, the manuscript identifies cultural assumptions of healing embedded in psychedelic study in favor of mechanistic causation that could be affecting a dismissal of the value of the ritual context. The paper proposes considerations for alternative research design philosophy along with the notion that spiritual rituals viewed as ancient libraries of healing knowledge may introduce hypotheses that current scientific bias is preventing researchers from realizing.